Pengembangan SOP di Kantor Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Bandar Lampung - Penida, Vhica; Hasyim, Adelina; Fitriawan, Eng Helmy (Indonesia Journal of Educational Technology, 2018)
The purpose of this reaserch was to analyze and explain the conditions and potential service quality of the Office DPM PTSP of of Bandar Lampung City and to develop products in the form of Standard Operating Procedures. This research was using research on the development of Standard Operating Procedures for DPM PTSP to see the level of community satisfaction with the services provided to these communities is known through the community satisfaction index.The results of the research obtaining a valid value of 63.61 can be categorized as feasible. The conclusion of this research is based on the calculation of the Public Satisfaction Index which refers to KEPMENPAN Number KEP / 25 / M.PAN / 2/2004, the index number is 71.83 which is in the interval 62.51 - 81.25, so the quality of public services is at the level of